1994
DOI: 10.1176/ajp.151.3.421
|View full text |Cite
|
Sign up to set email alerts
|

A model of homelessness among male veterans of the Vietnam War generation

Abstract: Individual vulnerability to homelessness is most likely due to a multiplicity of psychiatric and nonpsychiatric factors, with independent influences emerging at each of four discrete time periods. In view of this complex pattern of influences, prevention efforts directed at individuals must address a very broad range of adjustment problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Our data suggest that qualitative alterations in drug usage are more pronounced in southern Somalia. This notion would imply potential threats for the peace-building process in general (e.g., drug-related criminality) and the reintegration of former combatants into civilian society in particular [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that qualitative alterations in drug usage are more pronounced in southern Somalia. This notion would imply potential threats for the peace-building process in general (e.g., drug-related criminality) and the reintegration of former combatants into civilian society in particular [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combat experience and sequelae of trauma such as posttraumatic stress disorder (PTSD) have shown modest links to becoming homeless (Metraux, Clegg, Daigh, Culhane, & Kane, 2013;Rosenheck & Fontana, 1994). However, a majority of homeless veterans served during peacetime eras (Rosenheck, Frisman, & Chung, 1994) and thus were not exposed to combat.…”
Section: Introductionmentioning
confidence: 99%
“…1; 7; 13;20 The cumulative risk model has also been applied to homeless veterans and has shown that additional risk factors such as combat exposure, wartime trauma and post-traumatic stress disorder increase vulnerability to homelessness. 21 …”
Section: Introductionmentioning
confidence: 99%